Economic Recovery Strategies for the SME Sector Following the COVID-19 Pandemic - Rizqi Rizqi Maulana; Hancrisliana Santoso; Dwi Anggraeni; Anggie Davina Putri; Dhanu Wiguno; Ahmad Setiawan Nuraya (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The COVID-19 pandemic has dealt a severe blow to Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with 83% of businesses affected, 50% forced to close, and 63.9% experiencing a revenue decline of more than 30%. This study aims to analyze MSME economic recovery strategies post-COVID-19 pandemic by integrating elements of digitalization, business resilience, and government recovery policies. Using a qualitative approach through literature review and document analysis, this study synthesizes data from scientific journals, official government publications, and statistical reports. The results indicate that recovery strategies encompassing the National Economic Recovery Program (PEN), People’s Business Credit (KUR), tax incentives, credit restructuring, and digitalization yielded moderate to significant results. Digitalization has been a key driver of recovery, with 25.5 million SMEs joining the digital ecosystem by July 2024, and many reporting a 20–40% increase in revenue. Overall, SMEs’ contribution to GDP rose to 61.07% in 2024, surpassing pre-pandemic levels, while employment absorption remained stable at 97% of the total national workforce. However, the recovery remains uneven across business scales and regions, with ultra-micro businesses only reaching 75–80% of pre-pandemic levels, compounded by low digital literacy and infrastructure gaps between urban and rural areas.